Analisis Kinerja Keuangan Bank Syariah Indonesia (BSI) Dengan Metode Sharia Conformity And Profitability (SCnP) - Nanda Zukhrufi Prabowo; Sucik Lestari; Salwa Yuliana Chumaeroh; Elza Nova Fajria; Vira Fitriawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study employs a qualitative approach with an analysis of the financial statements of Bank Syariah Indonesia (BSI) for the period 2018-2022, obtained from BSI's official website. The method used is the Sharia Conformity and Profitability (SCnP) Model to classify the bank's performance into four quadrants based on sharia compliance and profitability. The analysis process involves calculating ratios such as sharia investment, sharia income, profit sharing, return on assets (ROA), return on equity (ROE), and profit margin. The results show that before the merger, the performance of state-owned sharia banks (BRIS, BNIS, BSM) displayed high ratios of sharia investment and profit sharing. However, after the merger, there was a significant increase in the ratios of ROA, ROE, and profit margin. According to the SCnP graph, all three state-owned sharia banks, both before and after the merger, were in the Lower Right Quadrant (LRQ), indicating high sharia compliance but low profitability. This result suggests that although sharia compliance has been met, profitability still needs to be improved.